2010
DOI: 10.1523/jneurosci.2848-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Retinal Deficits in a Zebrafish Pyruvate Dehydrogenase-Deficient Mutant

Abstract: Mutations in ubiquitously expressed metabolic genes often lead to CNS-specific effects, presumably because of the high metabolic demands of neurons. However, mutations in omnipresent metabolic pathways can conceivably also result in cell type-specific effects because of cell-specific requirements for intermediate products. One such example is the zebrafish noir mutant, which we found to be mutated in the pdhb gene, coding for the E1 ␤ subunit of the pyruvate dehydrogenase complex. This vision mutant is describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 47 publications
(55 reference statements)
7
22
0
Order By: Relevance
“…The ChAT antibody recognized only a band of around 70 kD on Western blots of mouse brain lysate (manufacturer's information at www.merckmillipore.com), and stained a pattern of cellular morphology and distribution consistent with amacrine cell labeling, identical to previous reports from the teleost retina (Yazulla and Studholme, 2001;Maurer et al, 2010).…”
Section: Antibody Characterizationsupporting
confidence: 70%
See 1 more Smart Citation
“…The ChAT antibody recognized only a band of around 70 kD on Western blots of mouse brain lysate (manufacturer's information at www.merckmillipore.com), and stained a pattern of cellular morphology and distribution consistent with amacrine cell labeling, identical to previous reports from the teleost retina (Yazulla and Studholme, 2001;Maurer et al, 2010).…”
Section: Antibody Characterizationsupporting
confidence: 70%
“…The TH antibody recognized only a band of around 60 kD on Western blots of cell lysates (manufacturer's datasheet), and stained a pattern of cellular morphology and location in the zebrafish retina identical to previous reports using another TH antibody (Maurer et al, 2010).…”
Section: Antibody Characterizationsupporting
confidence: 61%
“…Retinal degenerative diseases have been linked to mutations in energy metabolism and purine metabolism such as isocitrate dehydrogenase 3b, pyruvate dehydrogenase E1/2, nicotinamide mononucleotide adenylyltransferase, inosine monophosphate dehydrogenase, phosphodiesterase 6, and guanylyl cyclase (Aherne et al, 2004; Dizhoor, Boikov, & Olshevskaya, 1998; Farber & Lolley, 1974; Hartong et al, 2008; Maurer et al, 2010; Perrault et al, 2012; Taylor, Hurley, Van Epps, & Brockerhoff, 2004). Disruption of nutrient availability and metabolic regulation might play important roles in AMD and several models of retinitis pigmentosa (Punzo, Kornacker, & Cepko, 2009; Umino et al, 2006).…”
Section: Applicationsmentioning
confidence: 99%
“…Removal of glucose, inhibition of glycolysis, or deprivation of oxygen rapidly diminishes the ability of the retina to respond to light (Ames et al, 1992; Kang Derwent & Linsenmeier, 2000). Deficiencies of key enzymes and transporters in glucose metabolism cause retinal degeneration (Bui, Kalloniatis, & Vingrys, 2004; Maurer, Schonthaler, Mueller, & Neuhauss, 2010; Ochrietor & Linser, 2004). Neurons in the retina require metabolic support from glial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a few studies using Xenopus or skate (Raja erinacea), it has been shown that bipolar neurons can take up 5-HT (Schuette and Chappell, 1998;Schü tte, 1994). In the retina of zebrafish 5-HTimmunoreactive cells have also been detected among the amacrine population (Avanesov et al, 2005;Maurer et al, 2010). This domain contains cells with transcripts for tph1a, sertb, htr1aa, aanat1 and/or 2 (Bellipanni et al, 2002;Coon et al, 1999;Falcon et al, 2003;Norton et al, 2008;Zilberman-Peled et al, 2004).…”
Section: Pineal and Retinamentioning
confidence: 99%